(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research focuses on investigating the socio-economic conditions and challenges faced by the fishermen community in the Thoothukudi fisheries area. The study aims to achieve specific objectives, including examining the socio-economic status of the fishermen, identifying their primary problems, and proposing suitable policy measures for their improvement. Both primary and secondary data were utilized, with the primary data collected through a structured schedule and samples selected using a simple random sampling method. The research reveals that Thoothukudi’s fishing sector comprises mechanized and motorized categories, with the former showing better socio-economic development. During ban periods, providing alternative employment opportunities is crucial for the fishermen. Additionally, the study emphasizes the need for improved infrastructural facilities for fish catch storage and freezing, direct fish exports from Thoothukudi, and access to uninterrupted fuel at affordable rates for the fishing community’s well-being. The proposed policy measures aim to enhance the living conditions and economic prospects of the fishermen society in the region